PUTUSAN VERSTEK BERDASARKAN KETIDAKHADIRAN TERGUGAT DENGAN RELAAS YANG DI SAMPAIKAN KEPADA KEPALA DESA (STUDI KASUS PENGADILAN AGAMA MALANG) - samsia samsia; Ach. Faisol; Nurhasan Nurhasan (Fakultas Agama Islam UNISMA, 2020)
The verstek decision is a decision that the defendant does not attend at the beginning of the first trial and is still absent for the hearing on the following day. The impact when the defendant is not there is that the defendant does not know the trial schedule. Then the verstek trial was held by a summons from the trial through the substitute clerk of the court. The substitute clerk makes a summons at the residence of the defendant. If the defendant is not in the residence, then the call is sent through the family, neighbors or the village head. From the results of the judges' considerations, the Verstek decision was the verdict handed down by the judge outside the presence of the defendant. In the Verstek decision, there is a statement that the defendant is absent even though he has been properly summoned. In this study there are two legal remedies, ordinary legal remedies namely those used not yet fixed, such as technology, appeal and cassation and extraordinary remedies namely those used permanent legal force. For example, reconsideration and third party resistance.Â Keywords: verstek decision; relaas; village head